Household Strategies for Coping with Poverty and Social Exclusion in Post-Crisis Russia - Lokshin, Michael M.; Yemtsov, Ruslan (World Bank, Washington, DC, 2014)
What strategies have Russian households used, to cope with economic hardship in the wake of recent financial crisis? Which coping strategies have been most effective in reducing poverty for different groups of households? And how have people been able to adapt to the dramatic drop in formal cash incomes? The authors look at these questions using subjective evaluations of coping strategies used by household survey respondents to mitigate the effects of the Russian financial crisis on their welfare. The data come from two rounds (1996 and 1998) of the Russian Longitudinal Monitoring Survey. The results of their analysis show that a household's choice of survival strategy, strongly depends on its human capital: the higher its level of human capital, the more likely it is to choose an active strategy (such as finding a supplementary job, or increasing home production). Households with low levels of human capital, those headed by pensioners, and those whose members have low levels of education, are more likely to suffer social exclusion. To prevent poverty from becoming entrenched, the trend toward marginalization, and impoverishment of these groups of households, needs to be monitored, and targeted policy interventions need to be undertaken to reverse the trend.